Tethered balloon-borne measurements of turbulence and radiation during the Arctic field campaign Arctic Ocean 2018 in August/ September 2018 - Gottschalk, Matthias; Egerer, Ulrike (PANGAEA, 2021)
The tethered balloon system BELUGA (Balloon-bornE moduLar Utility for profilinG the lower Atmosphere) was operated from an ice floe next to IB ODEN (around 89°37.0' N , 40°46.5'E). The measurements were taken, as part of the project MOCCHA (Microbiology-Ocean-Cloud Coupling in the High Arctic), during the AO2018 (Arctic Ocean) campaign on 14 days in the period 18 August to 13 September 2018. For this campaign, a 9 m³ helium filled balloon with modular instrumentation was used. The dataset includes measurements of: - standard meteorological data based on a GRAW DFM-09 radiosonde with additional wind speed measurements by a Pitot-static probe - wind turbulence with a hot-wire anemometer (for instrument characteristics and methods see Egerer et al., 2019) - solar and terrestrial broadband radiation with upward and downward looking pyrgeometers and pyranometers (for instrument characteristics and methods see Egerer et al., 2019). The flights are summarized in the flight overview table (see "Further details"). Each flight includes measurements of standard meteorological data and in most cases of a second instrument.
Keywords: ABL; AO2018(MOCCHA); High Arctic; radiation; Tethered balloon; turbulence; vertical profiles